Determinasi Pola Susun dan Ketebalan Strip Log Core Papan Komposit - Sukma S. Kusumah; Bambang Subiyanto; Muh. Y. Massijaya (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
Waste from plywood industry has the potential as raw material in the manufacture of environmentally friendly composite board. The purpose of this research was to develop an environmentally friendly composite board from andong (Gigantochloa pseudoarundinaceae) bamboo veneer, rubber (Hevea brasiliensis) wood veneer, and waste of veneer peeling process ie log core by determining log core strip thickness and arrangement design optimum in composite board productions. Thicknesses of log core strip were 1.2 cm, 1.8 cm, and 2.4 cm. Arrangements of log core strip were type A and type B design. Composite boards were constructed from seven layers. Polyurethane was used as adhesive in composite board productions. The research result showed that the composite board made from andong bamboo veneer with type B in design and 1.8 cm thickness of log core strip performed better quality compared to those of other composite boards. The above type of composite boards fulfill Japanese Agricultural Standard No. 1516, 2003 for structural plywood, but not fulfill China Standard GB/T 19536 2004 plywood for container flooring. Based on result, the composite board was suitable for structural purposes such as door panels, and wall insulation